Quantificação de metacrilatos residuais e avaliação da liberação em saliva artificial a partir de resinas acrílicas para reembasamento imediato - Almeida, Fernando Gonçalves de (2008)
This work reports the development of analytical methods, using High Performance of Liquid Chromatography (HPLC), to quantify unreacted monomers from dental reline autopolimerizing acrylic resins. The quantification of these unreacted methacrylates is directly related with theirs toxicity, once that these may not only be irritant to the mucosa, but may also cause allergic and inflammatory reactions. In addition to this, high concentrations of unreacted monomers may cause alterations in physical and mechanical properties. For this purpose, three experimental resins (RE1, RE2 and RE3) and a commercial resin, Tokuyama Rebase Fast II (TKY), were selected to be analyzed. The development of these experimental resins has been carried out in cooperation with Faculty of Dentistry, Araraquara (FOAr - Unesp) and the dental corporation VIPI Ltda (Pirassununga, SP). The relevance of development these new resins is related to the necessity to have a national confectioned resin, because all resins used for these treatments are imported and reducing the cost of treatment. For quantification of unreacted monomers was necessary to extract them from the resins, so the extraction procedure was carried out in an ice-bath using methanol as extraction solvent. This procedure was validated through extractions in replicates. The monomers quantified were acetoacetoxy ethyl methacrylate (AAEM) from TKY resin, ethylene glycol dimethacrylate (EDMA), buthanediol dimethacrylate (BDMA) and cyclo hexyl metharylate (CHMA) all from experimental resins. Higher concentrations were found for experimental resins which the unreacted monomers concentrations range were, approximately 120μg/mL to 500μg/mL, 150μg/mL to 500μg/mL and 100 to 300μg/mL for resins RE3, RE1 e RE2, respectively Only for TKY resin was carried out a procedure to evaluate the quantity of unreacted monomer leached out in vitro in artificial saliva. There were found concentration in the range from 5.00 to 64.0μg/mL, in view of that the higher concentrations were leached from resin in the first 24 hours and after one week of artificial saliva immersion it was not observed the leaching of AAEM monomer.